Comparison of transforming growth factor-? (TGF-?) expression between diabetes mellitus associated carpal tunnel sydrome and idiopatic carpal tunnel sydrome - Deger, Ayse Nur; Deger, Hakki; Tayfur, Mahir; Balci, Mecdi Gurhan; Aksoy, Asude; Ekici, Mehmet Fatih; Moray, Melike Nalbant (E-Century Publishing Corp, 2016)
Background: Carpal Tunnel Syndrome (CTS) is a trap neuropathy which occurs when Nervous Medianus gets compressed in the carpal tunnel. Fibrosis of subsynovial connective tissue in etiopathogenesis of CTS occupies an important place. Systemic factors facilitate the formation of the syndrome. In this study, collagen structure and fibrosis of subsynovial connective tissue in patients with diabetic and idiopathic CTS cases were evaluated. Methods: Subsynovial connective tissue samples of 30 diabetes mellitus patients with CTS and 30 subsynovial connective tissue samples of idiopathic CTS cases were used in the study. Antibodies of Collagen Type I, Collagen Type II, Collagen Type III and Collagen Type VI were used to evaluate the collagen structure. Expression of Transforming Growth Factor-beta (TGF-beta), an important molecule held responsible of non-inflammatory fibrosis, was evaluated by comparison in both patient groups. Results: Specific staining was not observed in subsynovial connective tissue with Collagen Type I and Collagen Type II. Collagen Type III and Collagen Type VI were positive in subsynovial connective tissue and a significant difference in staining intensity was not observed in diabetic and idiopathic CTS group (P>0.01). Expression of Collagen Type III was seen as more intense in the vessel wall in the diabetic CTS group. (P<0.01). It was observed that TGF-beta expression in the diabetic group was weaker than the idiopathic CTS group. (P<0.01). Conclusion: Collagen Type VI is seen as the major component of the subsynovial connective tissue. Decrease in TGF-beta expression in subsynovial connective tissue was observed in diabetic CTS cases similar to the healing model of wounds in diabetic patients. We believe that microvascular changes and metabolic factors are effective more than TGF-beta expression in subsynovial connective tissue changes in diabetic patients with CTS. As a result, diabetic patients with CTS consisting the majority of CTS cases must be evaluated as a separate group of patients while histomorphological changes in CTS are evaluated.
Keywords: Carpal tunnel syndrome; diabetes mellitus; subsynovial connective tissue; transforming growth factor-beta